The Cretaceous/Paleogene (K‐Pg) boundary at the J Anomaly Ridge, Newfoundland (IODP Expedition 342, Hole U1403B). (8th June 2016) - Loroch, Dominik; Deutsch, Alexander; Berndt, Jasper; Bornemann, André
Abstract: We present results of an in‐situ geochemical study using laser‐ablation inductively coupled plasma–mass spectrometry (LA‐ICP‐MS) analyses along a 4.3 cm long section across the K‐Pg event bed, drilled during IODP Expedition 342 at J Anomaly Ridge south of St. John's, Newfoundland. This section comprises the Maastrichtian with a sharp boundary to the graded, between 1.5 and 1.8 cm thick ejecta layer with totally altered impact glass spherules, which in turn is topped by Danian sediments. The porous and clayey material required elaborate preparation in order to yield reliable data. The ejecta bed shows a highly variable depletion in rare earth elements that even results in strongly subchondritic concentrations. The Ce/Ce* varies strongly (0.81–34), Ni/Cr ranges from 0.38 to 2.79. The maximum platinum group elements (PGE) concentrations are located in one LA‐spot exactly at the basis of the ejecta layer; they amount (in μg g −1 ) to 0.35 (Rh), 1.64 (Pd), 2.79 (Pt), and 0.86 (Au). The Nb/Ta ratio increases in the Ma from 10 to 35.9 toward the ejecta horizon, which itself has higher Nb, Ta, Zr, and Hf concentrations than the background sedimentation, combined with low Nb/Ta ( 5–10), and low Zr/Hf ( 20–30). The overall result is that alteration processes changed totally the original geochemical characteristics of this K‐Pg spherule bed. To explain the exorbitant element mobility at distances of hundreds of μm, we discuss a combination of mostly reducing redox processes and interaction with organic compounds. This study demonstrates the high potential of in‐situ analyses with high spatial resolution at complex geological materials. Moreover, our results indicate that some caution is necessary in determining the projectile type in impactites via PGE ratios.